2018
DOI: 10.1920/re.ifs.2018.0144
|View full text |Cite
|
Sign up to set email alerts
|

Saving lives by tying hands: the unexpected effects of constraining health care providers

Abstract: The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…That said, there is an additional mechanism through which distances will be important -the time to get care. In a recent paper, Gruber et al (2018) show that reducing emergency department wait times by about 10% leads to a 14% reduction in mortality. 8 Also, see Thaddeus and Maine (1994) and Gabrysch and Campbell (2009) for reviews.…”
Section: Introductionmentioning
confidence: 99%
“…That said, there is an additional mechanism through which distances will be important -the time to get care. In a recent paper, Gruber et al (2018) show that reducing emergency department wait times by about 10% leads to a 14% reduction in mortality. 8 Also, see Thaddeus and Maine (1994) and Gabrysch and Campbell (2009) for reviews.…”
Section: Introductionmentioning
confidence: 99%
“…6 Gruber et al (2018) show that wait time might affect the intensity of medical treatment in the Emergency Department.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is shown that a 10-percent increase in the time required to reach a patient experiencing a cardiovascular episode (20% of a standard deviation from a mean of 28 minutes) increases the probability of a life-threatening condition by 9 percent (8% of a standard deviation from a mean of 45%) and the likelihood of patient mortality by 49 percent (10% of a standard deviation from a mean of 4%). 8 In support of the idea that time matters, Gruber et al (2018) show that reducing the time spent in the waiting room of an emergency department by 10 percent reduces mortality by 14 percent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has found that health providers increase their use of procedures that are incentivized in reimbursement contracts (Hennig-Schmidt et al 2011), and this increase is often, but not always (Celhay et al 2019), at the expense of non-incentivized tasks (Shearer et al 2018;Dumont et al 2008;Gruber et al 2018). Our paper is the first to assess whether incentivizing the demand for certain procedures leads to a deterioration in the use or quality of others.…”
Section: Introductionmentioning
confidence: 91%